Health‐related Research Ethics and Social Value: Antibiotic Resistance Intervention Research and Pragmatic Risks. (18th March 2019) - Munthe, Christian; Nijsingh, Niels; de Fine Licht, Karl; Joakim Larsson, D.G.
Abstract: We consider the implications for the ethical evaluation of research programs of two fundamental changes in the revised research ethical guideline of the Council for International Organizations of Medical Sciences. The first is the extension of scope that follows from exchanging "biomedical" for "health‐related" research, and the second is the new evaluative basis of "social value, " which implies new ethical requirements of research. We use the example of antibiotic resistance interventions to explore the need to consider the instances of what we term the pragmatic risks of such interventions to evaluate the social value of certain kinds of health‐related research. These (pragmatic) risks severely threaten the social value of interventions in every area where human and social responses significantly impact on their effectiveness. Thus, the social value of health‐related research needed to demonstrate its effectiveness depends on the extent and successful management of such risks. Research designed to take into account the management of pragmatic risks also gives rise to similar types of risks, and the potential for social value in light of those risks needs to be considered in ethical reviews based on the new guidelines. We argue that, to handle this new expanded task, the international system of research ethical review addressed by the guidelines needs institutional development.